Post-testicular sperm maturation in ancient holostean species - Dzyuba, Viktoriya; Shelton, William L; Hiott, Ana E; Cosson, Jacky; Bondarenko, Olga; Kholodnyy, Vitaliy; Dzyuba, Borys (Scientific reports, 2023)
Fish speciation was accompanied by changes in the urogenital system anatomy. In evolutionarily modern Teleostei, male reproductive tracts are fully separated from the excretory system, while in evolutionarily ancient Chondrostei and Holostei, the excretory and reproductive tracts are not separated. Sturgeon post-testicular sperm maturation (PTSM) occurring as a result of sperm/urine mixing is phenomenologically well described, while, in holosteans, functional intimacy of seminal ducts with kidney ducts and the existence of PTSM still need to be addressed. In Lepisosteus platostomus (Holostei), sperm samples were collected from testes (TS), efferent ducts (EDS), and Wolffian ducts (WDS). While WDS was motile, no motility was found in TS and EDS. The existence of PTSM was checked by in vitro PTSM procedure. After TS and EDS incubation in seminal fluid from WDS, no more than 5% motile spermatozoa were observed in TS, whereas in EDS the motility percentage was up to 75%. Experimental dyeing of urogenital ducts in gars and sturgeons revealed some differences in the interconnection between sperm ducts and kidneys. It is concluded that post-testicular sperm maturation occurs in gars and suggests that infraclass Holostei occupies an intermediate evolutionary position between Teleostei and Chondrostei in the anatomical arrangement of the urogenital system.
Keywords: Sperm Maturation; Sperm Motility; mužské pohlavní orgány; mužské pohlaví; motilita spermií; Fishes; zvířata; zrání spermie; Semen; ryby; testis; sperma; Spermatozoa; Testis; spermie; Male; Genitalia, Male; Animals